2007
DOI: 10.1021/jp0685075
|View full text |Cite
|
Sign up to set email alerts
|

Interpolymer Complexes Based on the Core/Shell Micelles. Interaction of Polystyrene-block-poly(methacrylic acid) Micelles with Linear Poly(2-vinylpyridine) in 1,4-Dioxane Water Mixtures and in Aqueous Media

Abstract: The size and structural changes of nanoparticles formed after the addition of poly(2-vinylpyridine), PVP, to block copolymer micelles of polystyrene-block-poly(methacrylic acid), PS-PMA, were studied by light scattering and atomic force microscopy. Due to the strong hydrogen bonding between PVP and PMA segments, complex structures based on the core/shell micelles form in mixed selective solvents. As proven by a combination of light scattering and atomic force microscopy, individual PS-PMA micelles are "glued" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…19 We and others have shown that under such conditions nonstoichiometric BIC are formed, which have a multilayer structure with a hydrophobic nonionic core, insoluble polyion complex layer, and hydrophilic shell of the excessive polyelectrolyte. [12][13][14][15][16][17][18] It was of interest to compare such complexes with soluble nonstoichiometric IPEC formed by linear homopolymers. 4 Unlike BICs, nonstoichiometric IPECs usually do not form core-shell aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We and others have shown that under such conditions nonstoichiometric BIC are formed, which have a multilayer structure with a hydrophobic nonionic core, insoluble polyion complex layer, and hydrophilic shell of the excessive polyelectrolyte. [12][13][14][15][16][17][18] It was of interest to compare such complexes with soluble nonstoichiometric IPEC formed by linear homopolymers. 4 Unlike BICs, nonstoichiometric IPECs usually do not form core-shell aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction of PSMs with oppositely charged linear polyelectrolytes, such as PEVP or poly(sodium carboxylates), can lead to formation of water-soluble nanosized complexes. [12][13][14][15][16][17][18][19] Such complexes have a multilayer structure with a hydrophobic nonionic core, intermediate water-insoluble polyion complex layer, and surrounding hydrophilic shell of the excessive polelectrolyte. [12][13][14][15][16][17][18] Previous work 19 has studied the dispersion stability of such BICs in aqueous media as a function of the composition and chemical nature of the reacting polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a dialysis of turbid water-rich mixtures in basic aqueous buffers results in the dissolution of polymer complexes in the form of soluble nanoparticles. Our previous study also shows that PS-PMA/PVP nanoparticles with a various PVP-to-PMA ratio are stable in a broad range of pH [3].…”
Section: Introductionmentioning
confidence: 66%
“…In our recent article [3], we described a simple strategy how one can prepare relatively stable micelles containing both weak polyacid, that is, poly(methacrylic acid) (PMA), and weak polybase, that is, poly(2-vinylpyridine) (PVP), with kinetically frozen polystyrene (PS) core, by dialysis from 1,4-dioxane-rich solutions into water. We took advantage from the fact that PMA forms a very stable complex with PVP in organic media, e.g., in 1,4-dioxanerich aqueous solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation